UV-thermal dual-curing adhesive as well as preparation method and application thereof

The combination of existing adhesives when combining UV photocuring and thermal curing is solved by using a specific proportion of epoxy resin, photoinitiator, thermal initiator and nanosilicon dioxide/silicon powder in UV-thermal double curing adhesives. The problems of incomplete curing and poor bonding performance achieve high strength and durability on metal substrates.

CN119320613AActive Publication Date: 2025-01-17HANGZHOU ZHIJIANG SILICONE CHEM +1

Patent Information

Application Number
CN202411122893.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-01-17
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The existing UV-thermal dual curing adhesives have problems such as incomplete curing, poor bonding performance and insufficient weathering performance when combining UV photocuring and thermal curing mechanisms, especially in the application of metal substrate bonding, which is difficult to meet complex environments. need.

Method used

Using specific proportions of epoxy resin, photoinitiator, thermal initiator and filler, including nanosilicon dioxide and silicon micropowder, the epoxy resin is modified by combining silicon materials of different particle sizes, and photoinitiator and thermal Initiator to achieve UV-thermal curing, improving bonding and weathering properties.

Benefits of technology

It realizes excellent bonding and weathering properties after complete curing of UV-thermal curing adhesives. It is suitable for surface bonding of metal substrates in automobiles, electronics and other fields, and can meet high strength and durability requirements in different application scenarios. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004995570490000021
    Figure BDA0004995570490000021
  • Figure BDA0004995570490000091
    Figure BDA0004995570490000091
Patent Text Reader

Abstract

The invention provides a UV-thermal dual-curing adhesive as well as a preparation method and application thereof, the UV-thermal dual-curing adhesive comprises epoxy resin, a photoinitiator, a thermal initiator and a filler in specific parts, and the filler comprises nano silicon dioxide with the D50 particle size of less than or equal to 100nm and silica powder with the D50 particle size of more than or equal to 0.5 mu m; the two silicon materials with different particle sizes are selected and matched to jointly form a filler to modify the epoxy resin, and meanwhile, the photoinitiator and the thermal initiator are added for initiation, so that the obtained adhesive can be subjected to UV-thermal dual curing, and the adhesive has excellent adhesive property and weather resistance after being completely cured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a UV-heat dual-curing adhesive and a preparation method and application thereof. Background Art

[0002] As an important industrial material, adhesives have been used in many fields such as electronics, communications, aviation, aerospace, and medical treatment. However, with the continuous improvement of material performance requirements, traditional single-curing adhesives can no longer meet the needs of use in complex environments. Therefore, the development of adhesives with dual curing mechanisms and better performance has become a research hotspot in the industry.

[0003] In terms of curing technology, UV light curing technology has become a hot topic in recent years due to its advantages of fast curing, high production efficiency, energy saving, and environmental protection. However, single UV light curing products have shortcomings such as incomplete curing, opaque or irregular products cannot be cured, and colored slurries interfere with absorbance and affect curing efficiency. In order to overcome these shortcomings, researchers began to explore dual-curing system products, among which UV-heat dual curing came into being.

[0004] The UV-heat dual curing method combines the advantages of UV light curing and heat curing. It can achieve rapid curing through UV light irradiation and improve the curing degree and performance through heating curing. This dual curing mechanism allows the adhesive to fully combine the advantages of the two curing methods during the curing process, thereby obtaining an adhesive product with better performance, especially in the structural bonding of metal substrates, which requires rapid initial positioning with UV light curing first, and then further improving its bonding force, tensile strength, and water resistance, high temperature resistance, and aging resistance through heat curing. However, in the development process of UV-heat dual curing adhesives, there are a series of technical challenges; the first is how to effectively combine the two mechanisms of UV light curing and heat curing to achieve the effect of dual curing; the second is how to control the curing speed and curing degree of the adhesive to meet the needs of different application scenarios; in addition, the bonding force, tensile strength, water resistance, high temperature resistance, aging resistance, and other properties of the adhesive also need to be considered.

[0005] At present, the products and research of UV-heat dual-curing adhesives mainly include the following systems: one is the two-component mixed system: (acrylic acid) free radical-(epoxy) cation mixed system, which has the characteristics of fast curing speed and high hardness, but because it simply physically mixes two types of resins and their curing agents with completely different reaction mechanisms, it leads to problems such as poor mutual solubility, poor storage stability and poor bonding performance; the second is the single-component system: a single-component system with acrylic acid double bonds and epoxy groups at both ends of the resin, which has the characteristics of excellent storage stability, but the resin has a large molecular weight, high viscosity, poor compatibility with acrylic acid resin and epoxy resin, and the glue viscosity is too high, resulting in poor process adjustability and poor bonding performance.

[0006] Therefore, in view of the above technical problems, it is urgent to develop a UV-thermal dual-curing adhesive with excellent bonding performance and weather resistance. Summary of the invention

[0007] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a UV-heat dual-curing adhesive and a preparation method and application thereof. The UV-heat dual-curing adhesive has excellent bonding performance and weather resistance, is suitable for bonding the surface of metal substrates, and can be widely used in multiple fields such as automobiles, electronics, and communications.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a UV-heat dual-curing adhesive, wherein the UV-heat dual-curing adhesive comprises the following components in parts by weight:

[0010]

[0011] The filler includes D 50 Nano-silicon dioxide with a particle size of ≤100nm and D 50 Silica powder with particle size ≥0.5μm.

[0012] The UV-heat dual-curing adhesive provided by the present invention comprises specific amounts of epoxy resin, photoinitiator, thermal initiator and filler, and the filler is limited to D 50 Nano-silicon dioxide with a particle size of ≤100nm and D 50 Silicon powder with a particle size of ≥0.5μm; by selecting the above silicon materials with different particle sizes to form a filler to modify the epoxy resin, and adding two initiators, a photoinitiator and a thermal initiator, the resulting adhesive has the characteristics of UV-heat dual curing, and has excellent bonding performance and weather resistance after complete curing.

[0013] Wherein, the usage amount of the epoxy resin can be 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight or 40 parts by weight, etc.

[0014] The amount of the photoinitiator can be 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight or 5 parts by weight.

[0015] The amount of the thermal initiator can be 0.1 parts by weight, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 1 part by weight, 1.2 parts by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight or 3 parts by weight, etc.

[0016] The amount of the filler can be 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight or 70 parts by weight.

[0017] The D of the nano-silica 50 The particle size can be 100 nm, 70 nm, 60 nm, 50 nm, 40 nm, 30 nm, 20 nm or 10 nm, etc.

[0018] The D of the silicon powder 50 The particle size may be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 2 μm, 5 μm or 10 μm, etc.

[0019] Preferably, the D of the nano-silicon dioxide 50 The particle size is 40 to 80 nm; further limiting the D of the nano-silicon dioxide 50 When the particle size is within the above range, the bonding performance and weather resistance of the obtained UV-heat dual-curing adhesive after complete curing can be further improved.

[0020] Preferably, the silicon powder has a D 50 The particle size is 1 to 2 μm; further limiting the D 50 When the particle size is within the above range, the bonding performance and weather resistance of the obtained UV-heat dual-curing adhesive after complete curing can be further improved.

[0021] Preferably, the nano-silica is nano-silica surface-modified with (3-glycidoxypropyl)trimethoxysilane.

[0022] Preferably, the silicon micropowder is silicon micropowder surface-modified with (3-glycidoxypropyl)trimethoxysilane.

[0023] In the present invention, there is no special restriction on the sources of the (3-glycidoxypropyl)trimethoxysilane surface-modified nano-silica and (3-glycidoxypropyl)trimethoxysilane surface-modified silicon micropowder, and they can be directly purchased from the market or prepared by themselves.

[0024] Preferably, the mass ratio of the nano-silicon dioxide to the silicon powder is 1:(5-35), for example, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30 or 1:35, etc.

[0025] Preferably, the epoxy resin includes any one of alicyclic epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, vinyl epoxy resin, siloxane epoxy resin, hydrogenated bisphenol A epoxy resin or hydrogenated bisphenol F epoxy resin, or a combination of at least two thereof.

[0026] Preferably, the alicyclic epoxy resin includes any one or a combination of at least two of bis-(3,4-epoxycyclohexylmethyl) adipate, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, di-4-epoxycyclohexane, 1,2:5,6-diepoxyhexahydroindane, 4-vinylepoxycyclohexane, 3,4-epoxycyclohexyl methacrylate or 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester.

[0027] Preferably, the photoinitiator comprises a cationic photoinitiator.

[0028] Preferably, the cationic photoinitiator includes any one of aromatic iodonium salts, aromatic sulfonium salts, aromatic diazonium salts, aromatic phosphonium salts or aromatic ferrocenium salts, or a combination of at least two thereof.

[0029] Preferably, the aromatic iodonium salt includes any one of diaryl pentafluorobenzene boric acid iodonium salt, diaryl hexafluorophosphate iodonium salt or diaryl hexafluoroantimonate iodonium salt or a combination of at least two thereof.

[0030] Preferably, the aromatic sulfonium salt includes triaryl sulfonium hexafluoroantimonate salt and / or triaryl sulfonium hexafluorophosphate salt.

[0031] Preferably, the ferrocenium salt comprises ferrocenium hexafluorophosphate.

[0032] Preferably, the thermal initiator comprises a cationic thermal initiator.

[0033] Preferably, the cationic thermal initiator includes any one of CXC1612, Vicbase TC3631, Vicbase TC3632, Vicbase TC3634, CTI-100, CTI-200 or CTI-300, or a combination of at least two thereof.

[0034] Preferably, the UV-heat dual-curing adhesive further includes a reactive diluent.

[0035] Preferably, the content of the active diluent in the UV-heat dual-curing adhesive is 10 to 40 parts by weight, for example, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight or 40 parts by weight.

[0036] Preferably, the active diluent includes any one or a combination of at least two of an alkenyl ether active diluent, a vinyl ketone acetal active diluent, an epoxy active diluent, an epoxidized triglyceride active diluent, an oxetane active diluent or a mixed active diluent containing an epoxy group and an enol ether group.

[0037] Preferably, the alkenyl ether active diluent includes any one or a combination of at least two of triethylene glycol divinyl ether (DVE-3), 4-hydroxybutyl vinyl ether (HBVE) or glycerol carbonate propenyl ether (PEPC);

[0038] Preferably, the oxetane active diluent includes any one or a combination of at least two of 3-ethyl-3-oxetanemethanol, 3-ethyl-3-chloromethyloxetane, 3,3-[oxybismethylene]bis[3-ethyl]oxetane, 3-ethyl-3-[(2-ethyl)-hexyloxymethyl]oxetane, 3-ethyl-3-[(benzyloxy)methyl]oxetane, 3-ethyl-3-[(phenoxy)methyl]oxetane or 3-ethyl-3-allylmethoxyoxetane.

[0039] Preferably, the UV-heat dual-curing adhesive also includes a thixotropic agent.

[0040] Preferably, the content of the thixotropic agent in the UV-heat dual-curing adhesive is 1 to 10 parts by weight, for example, 1 part by weight, 2 parts by weight, 4 parts by weight, 6 parts by weight, 8 parts by weight or 10 parts by weight.

[0041] Preferably, the thixotropic agent comprises fumed silica and / or precipitated silica.

[0042] Preferably, the UV-heat dual-curing adhesive also includes an antioxidant.

[0043] Preferably, the content of the antioxidant in the UV-heat dual-curing adhesive is 0.1 to 2 parts by weight, for example, 0.1 parts by weight, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight, 1 part by weight, 1.3 parts by weight, 1.6 parts by weight, 1.9 parts by weight or 2 parts by weight.

[0044] Preferably, the antioxidant comprises any one of aromatic amine antioxidants, ketoamines, aldehyde amines or hindered phenol antioxidants, or a combination of at least two thereof.

[0045] Preferably, the aromatic amine antioxidant comprises diaryl secondary amine and / or p-phenylenediamine.

[0046] Preferably, the hindered phenol antioxidant includes one of 2,6-di-tert-butyl-4-methylphenol, antioxidant AO-20 or antioxidant 1076, or a combination of at least two of them.

[0047] In a second aspect, the present invention provides a method for preparing the UV-heat dual-curing adhesive as described in the first aspect, the preparation method comprising: mixing an epoxy resin, a photoinitiator, a thermal initiator, a filler, an optional active diluent, an optional antioxidant and an optional thixotropic agent under yellow light conditions to obtain the UV-heat dual-curing adhesive.

[0048] Preferably, the preparation method comprises: under yellow light conditions, firstly mixing the epoxy resin, the photoinitiator and the active diluent evenly, adding the thixotropic agent and mixing evenly, then adding the nano-silicon dioxide and mixing evenly, then adding the silicon micropowder and mixing evenly, then adding the antioxidant and mixing evenly, and finally adding the thermal initiator and mixing evenly to obtain the UV-heat dual-curing adhesive.

[0049] In a third aspect, the present invention provides a use of the UV-heat dual-curing adhesive as described in the first aspect in bonding metal substrates.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] The UV-heat dual-curing adhesive provided by the present invention comprises specific portions of epoxy resin, photoinitiator, thermal initiator and filler, and the filler comprises D 50 Nano-silicon dioxide with a particle size of ≤100nm and D 50 Silica powder with a particle size of ≥0.5μm; by selecting the above-mentioned silica and silica powder with different particle sizes to form a filler together to modify the epoxy resin, and at the same time adding two initiators, a photoinitiator and a thermal initiator, to initiate the adhesive, so that the obtained adhesive can be UV-heat dual-cured, and has excellent bonding performance and weather resistance after complete curing. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0053] Some of the raw material information involved in the following examples and comparative examples are as follows:

[0054] (A) Epoxy resin

[0055] A-1: bis-(3,4-epoxycyclohexylmethyl) adipate;

[0056] A-2: 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarboxylate;

[0057] A-3: 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester.

[0058] (B) Photoinitiator

[0059] B-1: diphenyl-(4-phenylthio)phenyl sulfonium hexafluoroantimonate.

[0060] (C) Thermal initiator

[0061] C-1: CXC1612, purchased from King's Chemical, USA.

[0062] (D) Filling

[0063] D-1-50: Nano-silica surface modified with (3-glycidoxypropyl)trimethoxysilane, D 50 The particle size is 50 nm, and it is obtained by mixing (3-glycidoxypropyl)trimethoxysilane and unmodified nano-silica in a mass ratio of 6:1 in toluene at 90°C for 6 hours;

[0064] D-2-70: Nano-silica surface modified with (3-glycidoxypropyl)trimethoxysilane, D 50 The particle size is 70 nm, obtained by mixing (3-glycidoxypropyl)trimethoxysilane and unmodified nano-silica in a mass ratio of 6:1 in toluene at 90°C for 6 hours;

[0065] D-3-100: Nano-silica surface modified with (3-glycidoxypropyl)trimethoxysilane, D 50 The particle size is 100 nm, and it is obtained by mixing (3-glycidoxypropyl)trimethoxysilane and unmodified nano-silica in a mass ratio of 6:1 in toluene at 90°C for 6 hours;

[0066] D-4-150: Nano-silica surface modified with (3-glycidoxypropyl)trimethoxysilane, D 50 The particle size is 150 nm, and is obtained by mixing (3-glycidoxypropyl)trimethoxysilane and unmodified nano-silica in a mass ratio of 6:1 in toluene at 90°C for 6 hours;

[0067] D-5-50: Unmodified nano-silica, D 50 Particle size is 50nm;

[0068] D-6-0.3: Silica powder surface modified with (3-glycidoxypropyl)trimethoxysilane, D 50The particle size is 0.3 μm, obtained by mixing (3-glycidoxypropyl)trimethoxysilane and unmodified silica powder in a mass ratio of 1:2 in toluene at 90°C for 6 hours;

[0069] D-7-0.5: Silica powder surface modified with (3-glycidoxypropyl)trimethoxysilane, D 50 The particle size is 0.5 μm, obtained by mixing (3-glycidoxypropyl)trimethoxysilane and unmodified silica powder in a mass ratio of 1:2 in toluene at 90°C for 6 hours;

[0070] D-8-1.0: Silica powder surface modified with (3-glycidoxypropyl)trimethoxysilane, D 50 The particle size is 1.0 μm, obtained by mixing (3-glycidoxypropyl)trimethoxysilane and unmodified silica powder in a mass ratio of 1:2 in toluene at 90°C for 6 hours;

[0071] D-9-2.0: Silica powder surface modified with (3-glycidoxypropyl)trimethoxysilane, D 50 The particle size is 2.0 μm, obtained by mixing (3-glycidoxypropyl)trimethoxysilane and unmodified silica powder in a mass ratio of 1:2 in toluene at 90°C for 6 hours;

[0072] D-10-3.0: Silica powder surface modified with (3-glycidoxypropyl)trimethoxysilane, D 50 The particle size is 3.0 μm, obtained by mixing (3-glycidoxypropyl)trimethoxysilane and unmodified silica powder in a mass ratio of 1:2 in toluene at 90°C for 1 h;

[0073] D-11-2.0: Unmodified micro powder, D 50 The particle size is 2.0μm.

[0074] (E) Active diluent

[0075] E-1: 3-ethyl-3-allylmethoxyoxetane.

[0076] (F) Thixotropic agent

[0077] F-1: Fumed silica.

[0078] (G) Antioxidants

[0079] G-1: hindered phenol antioxidant, specifically antioxidant AO-20.

[0080] Examples 1 to 12 Comparative Examples 1 to 5

[0081] Examples 1 to 12 and Comparative Examples 1 to 5 respectively provide a UV-heat dual-curing adhesive, and the components contained are shown in Table 1 and Table 2 respectively;

[0082] In Tables 1 and 2, the dosage units of each component are "parts by weight";

[0083] Table 1

[0084]

[0085] Table 2

[0086]

[0087] The preparation method of the UV-heat dual-curing adhesive provided in Examples 1 to 12 and Comparative Examples 1 to 5 comprises the following steps:

[0088] Under yellow light conditions, the epoxy resin, the active diluent and the cationic photoinitiator are first mixed uniformly in a high-speed dispersion tank, and heated to 80°C to dissolve the cationic photoinitiator, and then the high-speed dispersion tank is placed in a homogenizer and stirred at 1500rpm for 2 minutes, and then a thixotropic agent is added, and the mixture is placed in a homogenizer and stirred at 1500rpm for 2 minutes, and then nano-silicon dioxide is added and stirred at 1500rpm for 2 minutes in the homogenizer, and then silicon micropowder is added and placed in a homogenizer and stirred at 1500rpm for 2 minutes, and then an antioxidant is added and stirred at 1500rpm for 2 minutes, cooled, and finally a cationic thermal initiator is added and stirred at 1500rpm for 2 minutes (vacuum degassing), cooled, and then placed in a homogenizer and stirred at 1500rpm for 2 minutes (vacuum degassing), and then the mixture is loaded with a rubber tube and stored frozen to obtain the UV-heat dual-curing adhesive.

[0089] Performance Testing:

[0090] (1) Initial tensile shear strength: Tested according to the test method provided in GB / T7124-2008; the test substrates are: AlSi 12 / AlSi 12 , and anodized aluminum / anodized aluminum; curing conditions: using a 365nm LED UV light curing machine, first at an energy density of 150mW / cm 2 The film was cured under UV light for 4 seconds and then thermally cured at 80°C for 60 minutes.

[0091] (2) Tensile shear strength after double 85 aging: The samples were aged at 85°C / 85% for 1000 h and then tested according to the test method provided in GB / T7124-2008; the test substrates were: AlSi 12 / AlSi 12, and anodized aluminum / anodized aluminum; the curing conditions are: first at an energy density of 150mW / cm 2 The film was cured under UV light for 4 seconds and then thermally cured at 80°C for 60 minutes.

[0092] The UV-heat dual-curing adhesives provided in Examples 1 to 12 and Comparative Examples 1 to 5 were tested according to the above test method. The test results are shown in Table 3:

[0093] Table 3

[0094]

[0095] According to the data in Table 3, we can see that:

[0096] The UV-heat dual-curing adhesive provided in Examples 1 to 12 has excellent bonding performance and weather resistance and is used for bonding AlSi 12 / AlSi 12 , the initial tensile shear strength after full curing reaches 7.5~11.7MPa, and the tensile shear strength after double 85 aging is still as high as 6.9~11.5MPa; used for bonding anodized aluminum, the initial tensile shear strength after full curing reaches 7.3~10.6MPa, and the tensile shear strength after double 85 aging is still as high as 6.7~10.5MPa;

[0097] Among them, by further optimizing and limiting the particle sizes of silicon dioxide and silicon powder, as well as the mass ratio of the two, the UV-heat dual-curing adhesives provided in Examples 1 to 3 and Example 7 can achieve the best bonding performance and the best weather resistance performance.

[0098] By comparing the data of Example 1 and Comparative Examples 1 to 5, it can be seen that the particle size of the added silicon dioxide is too large (Comparative Example 1), the particle size of the added silicon powder is too small (Comparative Example 2), only silicon dioxide is used as a filler (Comparative Example 3), only silicon powder is used as a filler (Comparative Example 4), and no filler is added at all (Comparative Example 5), all of which will lead to a significant decrease in the bonding performance and weather resistance of the obtained UV-heat dual-curing adhesive.

[0099] The applicant declares that the present invention illustrates a UV-heat dual-curing adhesive and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A UV-heat dual-curing adhesive, characterized in that: The UV-heat dual-curing adhesive comprises the following components in parts by weight: The filler includes D 50 Nano-silicon dioxide with a particle size of ≤100nm and D 50 Silica powder with particle size ≥0.5μm.

2. The UV-heat dual-curing adhesive according to claim 1, characterized in that: The D of the nano-silica 50 Particle size is 40-80nm; Preferably, the silicon powder has a D 50 Particle size is 1-2 μm; Preferably, the nano-silica is nano-silica surface-modified with (3-glycidoxypropyl)trimethoxysilane; Preferably, the silicon micropowder is silicon micropowder surface-modified with (3-glycidoxypropyl)trimethoxysilane; Preferably, the mass ratio of the nano-silicon dioxide to silicon powder is 1:(5-35).

3. The UV-heat dual-curing adhesive according to claim 1 or 2, characterized in that: The epoxy resin includes any one of alicyclic epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, vinyl epoxy resin, siloxane epoxy resin, hydrogenated bisphenol A epoxy resin or hydrogenated bisphenol F epoxy resin, or a combination of at least two thereof; Preferably, the alicyclic epoxy resin includes any one or a combination of at least two of bis-(3,4-epoxycyclohexylmethyl) adipate, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexylcarboxylate, di-4-epoxycyclohexane, 1,2:5,6-diepoxyhexahydroindane, 4-vinylepoxycyclohexane, 3,4-epoxycyclohexyl methacrylate or 4,5-epoxycyclohexane-1,2-dicarboxylic acid diglycidyl ester.

4. The UV-heat dual-curing adhesive according to any one of claims 1 to 3, characterized in that: The photoinitiator comprises a cationic photoinitiator; Preferably, the cationic photoinitiator comprises any one or a combination of at least two of aromatic iodonium salts, aromatic sulfonium salts, aromatic diazonium salts, aromatic phosphonium salts or aromatic ferrocenium salts; Preferably, the aromatic iodonium salt includes any one of diaryl pentafluorobenzene borate iodonium salt, diaryl hexafluorophosphate iodonium salt or diaryl hexafluoroantimonate iodonium salt or a combination of at least two thereof; Preferably, the aromatic sulfonium salt comprises triaryl sulfonium hexafluoroantimonate salt and / or triaryl sulfonium hexafluorophosphate salt; Preferably, the ferrocenium salt comprises ferrocenium hexafluorophosphate.

5. The UV-heat dual-curing adhesive according to any one of claims 1 to 3, characterized in that: The thermal initiator includes a cationic thermal initiator.

6. The UV-heat dual-curing adhesive according to any one of claims 1 to 4, characterized in that: The UV-heat dual-curing adhesive also includes a reactive diluent; Preferably, the content of the active diluent in the dual-cure adhesive is 10 to 40 parts by weight; Preferably, the reactive diluent includes any one or a combination of at least two of an alkenyl ether reactive diluent, a vinyl ketal reactive diluent, an epoxy reactive diluent, an epoxidized triglyceride reactive diluent, an oxetane reactive diluent, or a mixed reactive diluent containing an epoxy group and an enol ether group; Preferably, the alkenyl ether active diluent includes any one or a combination of at least two of triethylene glycol divinyl ether, 4-hydroxybutyl vinyl ether or glycerol carbonate propenyl ether; Preferably, the oxetane diluent includes any one or a combination of at least two of 3-ethyl-3-oxetanemethanol, 3-ethyl-3-chloromethyloxetane, 3,3-[oxybismethylene]bis[3-ethyl]oxetane, 3-ethyl-3-[(2-ethyl)-hexyloxymethyl]oxetane, 3-ethyl-3-[(benzyloxy)methyl]oxetane, 3-ethyl-3-[(phenoxy)methyl]oxetane or 3-ethyl-3-allylmethoxyoxetane.

7. The UV-heat dual-curing adhesive according to any one of claims 1 to 6, characterized in that: The UV-heat dual-curing adhesive also includes an antioxidant; Preferably, the content of the antioxidant in the dual-cure adhesive is 0.1 to 2 parts by weight; Preferably, the antioxidant comprises any one or a combination of at least two of aromatic amine antioxidants, ketoamines, aldehyde amines or hindered phenol antioxidants; Preferably, the aromatic amine antioxidant comprises diaryl secondary amine and / or p-phenylenediamine; Preferably, the hindered phenol antioxidant includes one of 2,6-di-tert-butyl-4-methylphenol, antioxidant AO-20 or antioxidant 1076, or a combination of at least two of them.

8. A method for preparing the UV-heat dual-curing adhesive according to any one of claims 1 to 7, characterized in that: The preparation method comprises: mixing epoxy resin, photoinitiator, thermal initiator, filler, optional active diluent, optional antioxidant and optional thixotropic agent under yellow light conditions to obtain the UV-heat dual-curing adhesive.

9. The preparation method according to claim 8, characterized in that: The preparation method comprises: under yellow light conditions, firstly mixing epoxy resin, photoinitiator and active diluent evenly, adding thixotropic agent and mixing evenly, then adding nano silicon dioxide and mixing evenly, then adding silicon micro powder and mixing evenly, then adding antioxidant and mixing evenly, and finally adding thermal initiator and mixing evenly to obtain the UV-heat dual-curing adhesive.

10. Use of the UV-heat dual-curing adhesive as claimed in any one of claims 1 to 7 in bonding metal substrates.

Citation Information

Patent Citations

  • Preparation method for low thermal expansion coefficient and low moisture-penetrability UV-thermal dual curing adhesive

    CN109321188A

  • Low-viscosity filler composition and preparation method thereof

    CN109456620A

  • Modified epoxy bridge deck ultra-thin material interface binder and preparation method thereof

    CN114958261A

  • Packaging adhesive and application thereof

    CN117004356A

  • Photo-thermal dual-curing adhesive as well as preparation method and use method thereof

    CN117777915A

Cited By

  • Aluminum-based copper-clad plate and preparation method thereof

    CN120422528A

  • Photo-thermal dual-curing resin, composition, cured product as well as preparation method and application of photo-thermal dual-curing resin

    CN120737309A

  • A photothermal dual-curing resin, composition, cured product, and preparation method and application thereof

    CN120737309B